Spatial distribution of total petroleum hydrocarbons in surface sediments of Palk Bay, Tamil Nadu, India - Pitchaikkaran Raja (KeAi Communications Co., Ltd., 2022)
Palk Bay is a marine protected area with a sensitive ecosystem like coral reefs, seagrass meadows, and mangroves with rich biodiversity. Observations indicate that these ecosystems are at risk from organic contaminants like petroleum hydrocarbon. In view of this Total Petroleum Hydrocarbons (TPHs) were measured in the surface sediments from the Palk Bay. Sediment samples were extracted in n-hexane and quantified using a fluorescence spectrophotometer. The concentrations of TPH varied from 0.78 ± 0.28 to 2.70 ± 0.84 μg/g (wet wt.) and were relatively higher in southern region than the northern. Higher TPH levels at the Bay are attributed to the anthropogenic activities and hydrodynamic characteristics. Analysis of sediment texture and organic carbon can provide insights into the distribution of TPH. Significant correlation was found between the sediment texture with TPHs and TOC. The average proportions of sediment grain sizes were 88.39 ± 3.92% of sand, 70.54 ± 2.24% of loamy sand, 62.22 ± 3.76% of sandy loam, and 29.58 ± 5.59% silt loam. Silt and clay of sediment have more capacity to hold the TPH because of their particle size. This is in consonance with the observed TOC levels in the range of 0.11 ± 0.05% and 2.78 ± 1.12% (dry weight). TPH concentrations are observed within the permissible limits and the data may serve as baseline information for identifying pristine coastal ecosystems like Palk Bay.